'The Trouble with Normal': (re)imagining sexuality education with young people. Issue 2 (4th March 2018) - Coll, Leanne; O'Sullivan, Mary; Enright, Eimear
Abstract: What do young people believe sexuality education ought to be about? It is within the absence of a sustained and critical consideration of the possibilities and politics of engaging in research with rather than for young people in the reimagining of sexuality education that this paper is positioned. Data were generated as part of an 18-month Youth Participatory Action Research study in one co-educational secondary school with 43 student co-researchers (15–17 years). The findings presented are not intended to provide conclusive statements about future directions for sexuality education, but rather provide a platform on which to discuss how young people's ideas align with or diverge from current practice and debates surrounding what sexuality education should, could or ought to be about.